Determination of TH1 and TH2 cytokine polarization according to parturition type in dairy cows - Koc, Oznur Yilmaz; Risvanli, Ali (Bmc, 2026)
Background The study aimed to determine the polarization of T helper (Th) 1 and Th2 cytokines in cows during normal parturition and dystocia. Methods We utilized 180 cows divided into two groups - normal parturition (NP) and dystocia (D). During the second stage of parturition, blood samples were taken from the cows. Results We then measured the concentrations of Th1 (Tumor Necrosis Factor-alpha (TNF-alpha), Interferon-gamma (IFN-gamma), Interleukin (IL)-2,) and Th2 (IL-5, IL-10, IL-4) cytokines in both groups using a commercial ELISA kit (Bio-Tek Instruments; USCN Life Science). Normality analysis was performed between the two groups, then independent t-test was performed for data that met parametric assumptions, while Mann Whitney U test was performed for data that did not meet parametric assumptions. Our findings indicate that the levels of TNF-alpha (67.20 +/- 9.95 pg/mL), IL-2 (519.55 +/- 60.15 pg/mL), IL-5 (151.33 +/- 94.28 pg/mL) (P<0.001); IL-4 (915.84 +/- 53.56 pg/mL), IL-10 (298.70 +/- 19.80 pg/mL) (P<0.01) in the D group significantly decreased in comparison to the NP group. The study found no significant difference in serum IFN-gamma levels between the NP and D groups. (P>0.05). Conclusions In analyzing the Th1/Th2 polarization balance in cows with NP, it concluded that this balance shifted towards Th2. As a result, it was derived that boosting humoral immunity would be apt, by implementing measures in this direction
Keywords: Cow; Parturition; Dystocia; Cytokine